2010 International Students and Young Scientists Workshop "Photonics and Microsystems" 2010
DOI: 10.1109/stysw.2010.5714167
|View full text |Cite
|
Sign up to set email alerts
|

Effect of acidic environment on the shape and size of the 1D nano-and microstructures of zinc oxide

Abstract: In this paper we presented influence of acidity on nanopowder structure prepared in reaction of precipitation. Zinc oxide was prepared from zinc nitrate and sodium hydroxide with the participation of the microwave field. The investigation revealed that the grain size of zinc oxide and their microstructure significantly depends on the solution pH. The microstructures obtained in the more alkaline reaction conditions have greater the aspect ratio.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2017
2017

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 11 publications
0
1
0
Order By: Relevance
“…There are many examples of descriptions of this process indicating different reaction steps, which are based on the equilibrium between the precipitation and dissolution of zinc oxide/hydroxide [ 15 ]. It is complicated because every factor of procedure, such as the kind and amount of reagents [ 16 , 17 ], time [ 18 ], and the temperature [ 12 ] of the reaction, has a significant influence on the obtained particles. It could be concluded that a smaller concentration of zinc nitrate and HMT, resulted in less zinc oxide (hydroxide), with a smaller average number of particles, being deposited on the surface.…”
Section: Introductionmentioning
confidence: 99%
“…There are many examples of descriptions of this process indicating different reaction steps, which are based on the equilibrium between the precipitation and dissolution of zinc oxide/hydroxide [ 15 ]. It is complicated because every factor of procedure, such as the kind and amount of reagents [ 16 , 17 ], time [ 18 ], and the temperature [ 12 ] of the reaction, has a significant influence on the obtained particles. It could be concluded that a smaller concentration of zinc nitrate and HMT, resulted in less zinc oxide (hydroxide), with a smaller average number of particles, being deposited on the surface.…”
Section: Introductionmentioning
confidence: 99%